Analysis of Arg-Gly-Asp mimetics and soluble receptor of tumour necrosis factor as therapeutic modalities for concanavalin A induced hepatitis in mice. (January 1997) - Bruck, R; Shirin, H; Hershkoviz, R; Lider, O; Kenet, G; Aeed, H; Matas, Z; Zaidel, L; Halpern, Z
Abstract : BACKGROUND/AIMS: It has been shown that synthetic non-peptidic analogues of Arg-Gly-Asp, a major cell adhesive ligand of extracellular matrix, prevented an increase in serum aminotransferase activity, as a manifestation of concanavalin A induced liver damage in mice. This study examined the effects of an Arg-Gly-Asp mimetic on liver histology and cytokine release in response to concanavalin A administration, and the efficacy of soluble receptor of tumour necrosis factor (TNF) alpha in preventing hepatitis in this model of liver injury. METHODS: Mice were pretreated with either the Arg-Gly-Asp mimetic SF-6, 5 or recombinant soluble receptor of TNF alpha before their inoculation with 10 mg/kg concanavalin A. Liver enzymes, histology, and the serum values of TNF alpha and interleukin (IL)6 were examined. RESULTS: The histopathological damage in the liver, and the concanavalin A induced release of TNF alpha and IL6 were significantly inhibited by the synthetic Arg-Gly-Asp mimetic (p < 0.001). Liver injury, manifested by the increase in serum aminotransferase and cytokines, as well as by histological manifestations of hepatic damage, was effectively prevented by pretreatment of the mice with the soluble TNF receptor (p < 0.001). CONCLUSIONS: This study confirms the efficacy of a synthetic Arg-Gly-Asp mimetic and soluble TNF receptor in the prevention of immune mediated liver damage in mice.